1995
DOI: 10.1007/bf02259659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and disease duration on parkinsonian motor scores under levodopa therapy

Abstract: One hundred and fifty patients suffering from Parkinson's disease were analysed for the expression of the motor symptoms during optimum response to levodopa therapy (subscale III of the Unified-Parkinson's Disease Rating Scale). Patients were grouped according to age (< or = 64, 65-74, > or = 75 years). Disease duration and daily levodopa dosage were similar in the three groups. Pooled residual scores for posture and gait impairment (PGI), tremor (T), rigidity (R) and distal motor impairment (DMI; hand and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
3
9
0
1
Order By: Relevance
“…The baseline characteristics do not enable us to predict a patient's surgical group, which comforts us in the homogeneity of our patients with PD waiting for surgery. Graphical representation at baseline confirms (1) a clear distinction between mania and depression; well known psychiatric sides of a bipolar disorders curve, and (2) a relation between disease duration and motor score, established long ago 38. Correlation circles of postsurgery characteristics at M3 and M6 reinforce our previous findings: surgery can influence psychiatric scores.…”
Section: Discussionsupporting
confidence: 84%
“…The baseline characteristics do not enable us to predict a patient's surgical group, which comforts us in the homogeneity of our patients with PD waiting for surgery. Graphical representation at baseline confirms (1) a clear distinction between mania and depression; well known psychiatric sides of a bipolar disorders curve, and (2) a relation between disease duration and motor score, established long ago 38. Correlation circles of postsurgery characteristics at M3 and M6 reinforce our previous findings: surgery can influence psychiatric scores.…”
Section: Discussionsupporting
confidence: 84%
“…This contrasts with the earlier age at onset of 45 years observed in our series, and this difference in age at onset is likely to explain, in part, this apparent controversy. It is of note that earlier-onset cases are overrepresented in this sample, and thus confirm previous findings from Selikhova et al [20] and others [4]. According to Selikhova et al [20], earlier-onset patients usually have relatively slow progression and the longest delay before the development of dementia, falling and need for residential care.…”
Section: Discussionsupporting
confidence: 79%
“…Despite effective symptomatic treatment, most patients eventually deteriorate with the passage of time [1,2,3,4,5,6,7,8,9,10,11,12,13]. The progression of PD is not predictable for individual cases - the figures differ between studies, depending on the type of study and initial treatment.…”
mentioning
confidence: 99%
“…Previous studies have reported that rigidity and bradykinesia [32], motor sequence [33], and disease severity [34] did not correlate with disease duration. Our findings of an insignificant correlation between trunk muscle tone and disease duration thus concurred with these reports.…”
Section: J Between-group Comparison Of Trunk Muscle Tonementioning
confidence: 95%